Analisis Pengaruh Indeks Pembangunan Manusia terhadap Tingkat Kemiskinan di Provinsi Jawa Barat pada Tahun 2021 - Muhamad Fathur Ramdani; Marizsa Herlina (Bandung Conference Series: Statistics, 2024)
Abstract. Practical courses are one of the courses in the curriculum of the Unisba Statistics Studies Program which are compulsory for students to take and work on their own under the guidance of a supervisor. The practice course aims to introduce students to the world of work, as well as to apply various statistical methods to the fields in which the student performs the practice course. The author carried out practical studies at the Central Statistical Agency of Garut district, which is located on Road Development No. 222, Sukagalih Village, Kidul Tarogong District, Garut District, West Java Province. The purpose of the report is to analyze the impact of the Human Development Index on poverty levels in the West Java Province in 2021. The analysis used in this report is a simple regression analysis using the variables Human Development Indicator (X) and Poverty Level Variable (Y). Based on the results of the analysis related to the influence of the human development index on the poverty rate in West Java province in 2021, it can be concluded that the Human development index has a negative and significant impact on the level of poverty in Western Java Province by 2021. Based on the R-square, it can be inferred as 0.583 or 58.3%, which means that 58.3% of the diversity of the poverty rate can be explained by the Human Development Index variable, while the remaining 41.7% can be described by another variable. Abstrak. Kuliah Praktik merupakan salah satu mata kuliah dalam kurikulum Program Studi Statistika Unisba yang wajib diambil oleh mahasiswa dan dikerjakan sendiri dengan petunjuk seorang pembimbing. Kuliah Praktik ini bertujuan untuk memperkenalkan dunia kerja kepada mahasiswa, selain itu juga untuk menerapkan berbagai metode statistika pada bidang dimana mahasiswa itu melakukan Kuliah Praktik. Penulis melakukan kegiatan Kuliah Praktik di Badan Pusat Statistik Kabupaten Garut yang beralamat di Jalan Pembangunan No. 222, Desa Sukagalih, Kecamatan Tarogong Kidul, Kabupaten Garut, Provinsi Jawa Barat. Laporan ini bertujuan untuk menganalisis pengaruh Indeks Pembangunan Manusia terhadap Tingkat Kemiskinan di Provinsi Jawa Barat pada tahun 2021. Analisis yang digunakan pada laporan ini adalah analisis regresi sederhana dengan menggunakan variabel Indeks Pembangunan Manusia (X) dan variabel Tingkat Kemiskinan (Y). Berdasarkan hasil analisis terkait pengaruh Indeks Pembangunan Manusia terhadap Tingkat Kemiskinan di Provinsi Jawa Barat pada tahun 2021, dapat disimpulkan bahwa Indeks Pembangunan Manusia berpengaruh negatif dan signifikan terhadap Tingkat Kemiskinan di Provinsi Jawa Barat pada tahun 2021. Berdasarkan R-square, dapat disimpulkan sebesar 0,583 atau 58,3% yang berarti sebesar 58,3% keragaman Tingkat Kemiskinan dapat dijelaskan oleh variabel Indeks Pembangunan Manusia. Sedangkan sisanya 41,7% dapat dijelaskan oleh variabel lain.